Automatic summarising of user stories in order to be reused in future similar projects. Issue 6 (11th November 2020) - Resketi, Mahsa Rahimi; Motameni, Homayun; Nematzadeh, Hossein; Akbari, Ebrahim
Abstract : User stories play an important role in agile development systems. In this study, a method of summarising user stories is proposed to reuse them in the future. To enhance the results, quality improvement should be made on user stories. It would help developers build better results, and it may also lead to omitting some essential information. To avoid such issues, user stories are duplicated in two exact similar groups, and quality improvement is made on one set while the other set remains unattained. With the help of a modified bag of words and a verb parser, a collection of keywords and key verbs are extracted for both groups. Afterwards, automatic user stories are made, and then an expert improves them. Next, some experts choose between the results and select the better ones. The result is evaluated by applying different experiments on the framework and prototype implementation on 14 data sets of a user story from industry and a fake data set from Duke University. The result showed 97% of micro F ‐measure and 93% of macro F ‐measure, which are promising. These new user stories can be used as the base user stories in future similar projects.